‘Assunta’ and ‘Ara’ UPLB’S first and fresh market tomato F1 hybrid varieties for off-season production (Lycopersicon esculentum Linn) (The Philippine Journal of Crop Science, 2010)
The tomato varietal improvement effort at the Institute of Plant Breeding led to the development of F1 hybrid varieties, ‘Assunta’ and ‘Ara’ for off-season production. The development of ‘Asunta’ and ‘Ara’ was among the first attempt of IPB to focus its breeding strategies towards exploitation of heterosis in yield, uniformity and vigor in F1 hybrids. The superiority of the two hybrids in terms of yield and tolerance to adverse environmental conditions during off season was shown in on-farm field trials conducted in major tomato growing areas in the country. The two hybrids were released as IPB varieties for off season production.